2004
DOI: 10.3354/meps274225
|View full text |Cite
|
Sign up to set email alerts
|

Parental effects in the European sardine Sardina pilchardus

Abstract: Positive parental effects, defined as the strategies displayed by sardine Sardina pilchardus adults to increase the survival of eggs and larvae, were studied off the coast of the Iberian Peninsula (Spain) by monthly sampling of eggs and larvae in Ría de Vigo, over a period of 4 yr. Two different parental strategies were observed over the spawning period: temporal variations in spawning intensity, and variation of egg quality. Sardine spawn outside the upwelling season, to avoid offshore transport of eggs and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 58 publications
(56 reference statements)
1
28
0
Order By: Relevance
“…Thus, adults were likely to have influenced the outcome of selective events through maternal contributions to larval size. Similar evidence for parental contributions to survivorship has been documented for a tropical reef fish by Vigliola & Meekan (2002), while, in clupeids, Riveiro et al (2004) found that adult European sardines Sardina pilchardus were capable of enhancing the survival of hatching larvae by altering the biochemical composition of eggs during the spawning season. However, the latter study did not investigate whether variations in parental investment in eggs influenced mortality within cohorts.…”
Section: Discussionmentioning
confidence: 62%
“…Thus, adults were likely to have influenced the outcome of selective events through maternal contributions to larval size. Similar evidence for parental contributions to survivorship has been documented for a tropical reef fish by Vigliola & Meekan (2002), while, in clupeids, Riveiro et al (2004) found that adult European sardines Sardina pilchardus were capable of enhancing the survival of hatching larvae by altering the biochemical composition of eggs during the spawning season. However, the latter study did not investigate whether variations in parental investment in eggs influenced mortality within cohorts.…”
Section: Discussionmentioning
confidence: 62%
“…However, the DT revealed that the peaks of fish eggs by themselves do not guarantee a high occurrence of fish larvae. This may be related to other factors, such as temperature and predation, which are the main causes of mortality in fish eggs (Riveiro et al 2004). …”
Section: Discussionmentioning
confidence: 99%
“…Lipids and proteins are 2 biochemical compounds that affect fish egg quality, and reports indicate that the lipid and protein contents of eggs vary from the onset of the spawning season to its end. Off the Iberian Peninsula, concentrations of lipids, carbohydrates, and proteins decrease in Sardina pilchardus eggs as the spawning season progresses from winter to mid-spring, suggesting that better-quality eggs are spawned at low winter temperatures and when larval food is less abundant, thereby enhancing larval growth and survival (Riveiro et al 2000(Riveiro et al , 2004.…”
Section: Introductionmentioning
confidence: 99%